PESONA DAN EKOSISTEM TENUN SONGKET TODO: ANALISIS PARIWISATA BUDAYA DI KAMPUNG TODO, KABUPATEN MANGGARAI, NUSA TENGGARA TIMUR - Mamut, Maria Yulianasti; Gusti Ayu Mahanavami; I Wayan Tantra; Wiryawan Suputra Gumi; Nyoman Parta (Journal of Innovation Research and Knowledge, 2025)
The diversity of cultural and weaving traditions in Indonesia creates a unique heritage. Kampung Todo in Manggarai Regency, with its flagship product, the Todo Songket Weaving Craft, has become a magnet for cultural tourism. This study aims to explore the appeal and contributions of the Todo songket weaving ecosystem, analyze its impact on the local community's livelihood, and examine the government’s support as a crucial factor in the context of cultural tourism in Kampung Todo, Manggarai Regency, East Nusa Tenggara. The research relies on primary and secondary data, employing data collection methods such as observation, interviews, and documentation studies. Data analysis was conducted using a qualitative descriptive approach. The findings reveal that the charm of Todo Songket Weaving continues to grow, supported by the availability of raw materials and increasingly innovative color variations. Modern technology, particularly social media, plays a significant role in promotion and information dissemination. The positive impact of Todo songket weaving on the local community includes economic benefits and meeting daily needs. Government support through training programs, provision of raw materials, and promotional assistance has also contributed to the development of Kampung Todo as an attractive cultural tourism destination.